2006
DOI: 10.1055/s-2006-925331
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Androgen-binding Protein (ABP) in Human Cardiac Myocytes

Abstract: Cardiomyocytes are known to be androgen targets. Changing systemic steroid levels are thought to be linked to various cardiac ailments, including dilated cardiomyopathy (DCM). The mode of action of gonadal steroid hormones on the human heart is unknown to date. In the present study, we used high-resolution immunocytochemistry on semithin sections (1 microm thick), IN SITU hybridization, and mass spectrometry to investigate the expression of androgen-binding protein (ABP) in human myocardial biopsies taken from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 17 publications
0
25
0
1
Order By: Relevance
“…It should, however, be noted that cardiac myocytes are targets for androgens. 36 Dilated cardiomyopathy has previously been associated with low levels of testosterone in men, 37 and Schock et al 38 demonstrated increased SHBG in cardiomyocytes of men with dilated cardiomyopathy. This is in line with our data on a positive association of SHBG and the inverse association of FT levels with NT-pro-BNP.…”
Section: Discussionmentioning
confidence: 98%
“…It should, however, be noted that cardiac myocytes are targets for androgens. 36 Dilated cardiomyopathy has previously been associated with low levels of testosterone in men, 37 and Schock et al 38 demonstrated increased SHBG in cardiomyocytes of men with dilated cardiomyopathy. This is in line with our data on a positive association of SHBG and the inverse association of FT levels with NT-pro-BNP.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment with DHEA prevents pulmonary vascular changes and RV hypertrophy, and prolongs survival in animal models of pulmonary hypertension (PH) (7,8). SHBG is expressed in myocytes of failing human hearts and in murine fetal lung epithelium, but its role in pulmonary vascular function has not been studied (9,10).…”
mentioning
confidence: 99%
“…Autoradiographic and biochemical studies previously demonstrated that murine and primate atrial and ventricular cardiomyocytes express androgen receptors that may affect myocardial structure and function (Krieg et al ., ; McGill et al ., ). In addition, molecular studies detected androgen receptor and androgen‐binding protein RNA in murine and human hearts (Marsh et al ., ; Schock et al ., ). Testosterone exposure affected both the nuclear and cytoplasmic distribution of these receptors, suggesting they are physiologically functional and that testosterone may directly regulate cardiomyocyte function, growth and hypertrophic remodelling (Lin et al ., ).…”
Section: Resultsmentioning
confidence: 97%